Participation in an online social policy discussion: Arguments in focus. (October 2017) - Lehti, Lotta; Kallio, Johanna
Highlights: The digital agora appears to be accessible also for the most disadvantaged. In our case study, personal experience as argument prevails. Polarization of opinions was uncommon, although not inexistent. Studying opinions as arguments pinpoints to different aspects of participation structure. Abstract: The paper investigates participation in digital agora through a case study analysing opinions as arguments. The material under scrutiny pertains to social policy: we explore nine comment threads from news sites following a news item on social policy research concerning social workers' opinions about the causes of poverty in four Nordic countries. The analysis concentrates on three argument types, all justifying the conclusion that Finnish social workers are rude. The argument types vary in terms of the obviousness of the link between justification and participants: The argument types of 'personal experience' and of 'irresponsibility of those claiming social assistance' display a rather clear link while the argument of 'national temperament' indicates less clearly who is participating. The analysis especially highlights the involvement of the most disadvantaged and the role of professional journalists. The arguments also refer to the discourses circulated, e.g. national stereotypes and the Nordic media discourse of blaming the social policy system while sympathising with the clients.